The predictive value of masticatory function for adverse health outcomes in older adults: a systematic review - Menke J. de Smit; Willemke Nijholt; Mieke H. Bakker; Anita Visser (Elsevier, 2024)
Masticatory function is associated with a variety of health outcomes. The aim of this systematic review is to clarify the predictive value of masticatory function for adverse health outcomes, such as frailty, sarcopenia and malnutrition, in older adults.An online literature search covered articles published in English or Dutch in three databases (PubMed, Embase and CINAHL, last searched November 4th 2022). Inclusion criteria were: an observational study design, focus on adults aged ≥65 years and evaluation of the association between masticatory function and health outcomes. Reviews and articles published before the year 2000 were excluded. Methodological quality and risk of bias were assessed using the Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies of the U.S. National Institutes of Health. Study population demographics, methods for assessing masticatory function, and the association between masticatory function and adverse health outcomes were extracted.From the 34 included studies, 5 studies had a prospective design, 2 had a retrospective design, and the other 27 studies had cross-sectional design. The majority of the studies were conducted in Japan (74%, n = 26). Twenty studies (59%) used one indicator for masticatory function, the other 41% used two (n = 9) or more (n = 5) indicators. Masticatory function was most frequently assessed with the maximum occlusal force (MOF) (79%, n = 27). The identified health outcomes were clustered into 6 categories: physical parameters and sarcopenia, history of falling, nutritional status, frailty, cognitive function and mortality.Despite the complex and multidimensional character of both masticatory function and most identified adverse health outcomes, some significant associations were reported. Prospective studies showed that reduced masticatory function in older adults is associated with incidence of frailty and frailty progression, cognitive decline and all-cause mortality. Regarding the other identified adverse health outcomes, i.e., physical measures and sarcopenia, history of falling and nutritional status, only cross-sectional studies were available and results were less concordant. As all prospective studies showed that reduced masticatory function in older adults is associated with adverse health outcomes, prevention of decline of masticatory function by adequate oral care may contribute to healthy ageing.